(untitled) (International Journal of Innovative Technologies in Economy, 2024)
This article delves into the assessment of the alignment of Lean practices within Algerian construction companies when implementing improvement approaches. It aims to contribute to a deeper understanding of the issues at hand and the anticipated impacts on managerial behavior as a result of implementing Lean construction approaches. These methodologies are seen as pivotal in reducing costs and lead times. This research is a vital component of an analysis that investigates how the implementation of Lean principles aligns with different company types and explores the potential improvements and benefits it can bring. This analysis has become more important as companies increasingly adopt new strategies and managerial values, and enhance their production tools in pursuit of new growth opportunities. These measures are essential for adapting to the growing challenges and changes in today’s socio-economic environment. In response to these challenges, we have initiated a study that examines the alignment of Lean practices. This study includes the creation of a questionnaire (133 questions) based on the fourteen Lean principles uses the IEMSE evaluation method. Its main purpose is to address the issue of varying levels of Lean practice implementation and to evaluate compatibility with the specific management systems employed within construction companies.